2015
DOI: 10.4049/jimmunol.1501361
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role and Therapeutic Control of the Lectin Pathway of Complement Activation in an Abortion-Prone Mouse Mating

Abstract: The abortion-prone mating combination CBA/J × DBA/2 has been recognized as a model of preeclampsia, and complement activation has been implicated in the high rate of pregnancy loss observed in CBA/J mice. We have analyzed the implantation sites collected from DBA/2-mated CBA/J mice for the deposition of the complement recognition molecules using CBA/J mated with BALB/c mice as a control group. MBL-A was observed in the implantation sites of CBA/J × DBA/2 combination in the absence of MBL-C and was undetectable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Among the down-regulated genes we selected for validation experiments HIST1H1B (encoding histone H1) and HIST1H4A (histone H4), and among the upregulated gene-list C3 (complement component 3), CAPNS1 (calpain, small subunit 1) and PLTP (phospholipid transfer protein). Among these, C3 and PLTP have also literature evidence for the involvement of RPL and/or function at the feto-maternal interface185859. For CAPNS1 a role in acute allograft rejection has been reported60.…”
Section: Methodsmentioning
confidence: 99%
“…Among the down-regulated genes we selected for validation experiments HIST1H1B (encoding histone H1) and HIST1H4A (histone H4), and among the upregulated gene-list C3 (complement component 3), CAPNS1 (calpain, small subunit 1) and PLTP (phospholipid transfer protein). Among these, C3 and PLTP have also literature evidence for the involvement of RPL and/or function at the feto-maternal interface185859. For CAPNS1 a role in acute allograft rejection has been reported60.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, its usefulness as a model of preeclampsia is limited. More recent studies in this model demonstrated that MBL and C1q deposition were evident at GD3.5 and C3 at GD6.5 indicating that complement activation occurred early in the implantation phase [62], similar to the BPH/5 mouse. If lectin pathway activation was controlled using either a molecule that binds MBL with high affinity (Polyman 2), MBL-A deficient mice, or anti-C5 antibody, fetal loss was prevented, consistent with an important role for lectin pathway activation in fetal loss.…”
Section: The Complement System In Stage 1 Of Placental Preeclampsiamentioning
confidence: 99%
“…Complement activation generates inflammatory mediators which facilitate a crucial danger signal to surrounding cells and migrating leucocytes . The lectin pathway, which is the most recently described complement activation pathway, has gained much interest in the development of pre‐eclampsia and IUGR . The lectin pathway consists of the pattern recognition molecules mannose‐binding lectin (MBL), ficolins (H‐, L‐ and M‐) and collectins liver‐1 (CL‐L1) and kidney‐1 (CL‐K1), together with the MBL‐associated serine protease (MASP)‐1, MASP‐2 and MASP‐3 and the regulatory MBL‐associated proteins of 19 kDa (MAp19) and 44 kDa (MAp44) .…”
Section: Introductionmentioning
confidence: 99%
“…The lectin pathway consists of the pattern recognition molecules mannose‐binding lectin (MBL), ficolins (H‐, L‐ and M‐) and collectins liver‐1 (CL‐L1) and kidney‐1 (CL‐K1), together with the MBL‐associated serine protease (MASP)‐1, MASP‐2 and MASP‐3 and the regulatory MBL‐associated proteins of 19 kDa (MAp19) and 44 kDa (MAp44) . MBL may be directly involved in the impairment of spiral artery remodelling and trophoblast invasion in early pregnancy . Furthermore, the pattern recognition molecules recognize not only pathogens but also necrotic or apoptotic cells .…”
Section: Introductionmentioning
confidence: 99%